Tailored interventions to support the implementation of the German national guideline on screening, diagnosis and treatment of alcohol-related disorders: a project protocol - Schulte, Bernd; Wensing, Michel (Sucht, 2019)
Background: The German Guideline on Screening, Diagnosis and Treatment of Alcohol Use Disorders aims to increase the uptake of evidence-based interventions for the early identification, diagnosis, prevention and treatment of alcohol-related disorders in relevant healthcare settings. To date, dissemination has not been accompanied by a guideline implementation strategy. The aim of this study is to develop tailored guideline implementation strategies and to field-test these in relevant medical and psycho-social settings in the city of Bremen, Germany. Methods: The study will conduct an impact and needs assessment of healthcare provision for alcohol use orders in Bremen, drawing on a range of secondary and primary data to: evaluate existing healthcare services; model the potential impact of improved care on public health outcomes; and identify potential barriers and facilitators to implementing evidence-based guidelines. Community advisory boards will be established for the selection of single-component or multi-faceted guideline implementation strategies. The tailoring approach considers guideline, provider and organizational factors shaping implementation. In field tests quality outcome indicators of the delivery of evidence-based interventions will be evaluated accompanied by a process evaluation to examine patient, provider and organizational factors. Outlook: This project will support the translation of guideline recommendations for the identification, prevention and treatment of AUD in routine practice and therefore contributes to the reduction of alcohol-related burden in Germany. The project is running since October 2017 and will provide its main outcomes by end of 2020. Project results will be published in scientific journals and presented at national and international conferences.